Structural Model Presentation for Readiness to Change Based on Achievement Motivation and Psychological Capital with Problem-Solving Mediation in Islamic Azad University of Roudehen Students - Salehi Roodposhti, Leila; Behboodi, Masoumeh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: The current research aimed to present a structural model for readiness to change based on achievement motivation and psychological capital with problem-solving mediation in students of Islamic Azad University, Roudehen. Methods and Materials: The research method was correlational using structural equation modeling, and the population included all undergraduate students at Islamic Azad University, Roudehen branch, in the academic year 2022-2023. The sample size comprised 220 individuals selected via multi-stage cluster random sampling and responded to the Readiness for Change Questionnaire by Sloo (2006), Hermans’ Achievement Motivation (1970), and Cassidy and Long’s (1996) Problem-Solving Styles questionnaire. Findings: The findings from the structural equation modeling using AMOS software indicated that the structural model of the study fits the collected data. Moreover, achievement motivation positively and significantly predicts readiness for change in students. Psychological capital also predicts readiness for change positively and significantly in students. Adaptive problem-solving strategies positively and maladaptive strategies negatively and significantly predict readiness for change in students. Conclusion: Both adaptive and maladaptive problem-solving strategies significantly mediate the relationship between achievement motivation and readiness for change, as well as between psychological capital and readiness for change in students.